Waktu Efektif dalam Dekomposisi Sampah Organik Rumah Tangga dengan Larva Lalat Tentara Hitam - Firra Rosariawari; Anatasia Wira Harianti (Prosiding ESEC, 2022)
Management and utilization of organic waste has not given significant results. The lack of community participation and the high cost of waste processing technology are the reasons for which there are no significant results. One way to degrade organic waste is by using microorganisms that can act as bioconversion agents of organic waste by using black soldierlarvae (Hermetia illucens). This study aims to determine the effevtive time in the process to be able to decompose organic waste that can be carried out by black soldier larvae. Larvae have reached the highest level to decompose waste.